1999
DOI: 10.1080/15216549900201703
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation induced by the Cu,Zn‐superoxide dismutase and hydrogen peroxide system

Abstract: SUMMARY: Cu, Zn-superoxide dismutase (SOD) can catalyze hydroxyl radical generation using H202 as a substrate. Lipid peroxidation induced by the Cu,Zn-SOD and H202 system was investigated. When linoleic acids micelles or phosphatidylcholine liposomes were incubated with Cu,Zn-SOD and H202, lipid peroxidation was gradually increased in a time-dependent manner.The extent of lipid peroxidation was proportional to Cu,Zn-SOD and H202 concentrations.Hydroxyl radical scavengers and copper chelator inhibited lipid per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…This result was not surprising because participants with serum HLD-C concentration ≥1.2 mmol/L had significantly higher plasma copper concentrations compared to participants with HDL-C <1.2 mmol/L in the current study, and a positive association between copper and HDL-C concentrations has been reported in previous studies ( 36 ). Cu-SOD and H 2 O 2 system induces lipid peroxidation ( 13 ). It has been reported that HDL is more susceptible to copper-induced oxidation than LDL when copper concentration is high ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was not surprising because participants with serum HLD-C concentration ≥1.2 mmol/L had significantly higher plasma copper concentrations compared to participants with HDL-C <1.2 mmol/L in the current study, and a positive association between copper and HDL-C concentrations has been reported in previous studies ( 36 ). Cu-SOD and H 2 O 2 system induces lipid peroxidation ( 13 ). It has been reported that HDL is more susceptible to copper-induced oxidation than LDL when copper concentration is high ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite being essential, excessive copper may mediate the formation of excessive damaging reactive oxygen species (ROS) via Haber-Weiss and Fenton-like reactions ( 11 ), which has been reported as a trigger for insulin resistance ( 12 ). The Cu-Superoxide dismutase (SOD) and hydrogen peroxide (H 2 O 2 ) system may induce lipid peroxidation ( 13 ), which is closely associated with diabetes ( 14 ). In addition, excess copper has been reported to reduce the relative abundance of short-chain fatty acid producing bacteria and increase the relative abundance of Corynebacterium , which collectively may promote metabolic inflammation and poor glucose control ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between Cu levels and lipid profile could be because of Cu on catalase and glutathione peroxidase, two enzymes that reduce hydrogen peroxidase and modulate oxidative stress and redox-mediated responses [ 93 ]. High serum Cu level inhibits glutathione reductase and reduces glutathione production, thus, altering lipid metabolism [ 94 , 95 ]. Furthermore, SOD activity is decreased with Cu deficiency which consequently increases the synthesis of hydroxyl free radicals that have a central link to atherosclerosis [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, copper also affects catalase and glutathione peroxidase (GSH Px) activity. Excessive copper also produces excessive copper chelate, indirectly inhibiting GSH reductase and reducing GSH production, affecting lipid metabolism [35,36].…”
Section: Discussionmentioning
confidence: 99%